The nonsense mutation MSH2 c.2152C>T shows a founder effect in Portuguese Lynch syndrome families. Issue 9 (26th April 2019) - Pinheiro, Manuela; Francisco, Inês; Pinto, Carla; Peixoto, Ana; Veiga, Isabel; Filipe, Bruno; Santos, Catarina; Maia, Sofia; Silva, João; Pinto, Pedro; Santos, Rui; Claro, Isabel; et al.
Abstract: The mutational spectrum of the MMR genes is highly heterogeneous, but specific mutations are observed at high frequencies in well‐defined populations or ethnic groups, due to founder effects. The MSH2 mutation c.2152C>T, p.(Gln718*), has occasionally been described in Lynch families worldwide, including in Portuguese Lynch syndrome families. During genetic testing for Lynch syndrome at the Portuguese Oncology Institutes of Porto and Lisbon, this mutation was identified in 28 seemingly unrelated families. In order to evaluate if this alteration is a founder mutation, haplotype analysis using microsatellite and SNP markers flanking the MSH2 gene was performed in the 28 probands and 87 family members. Additionally, the geographic origin of these families was evaluated and the age of the mutation estimated. Twelve different haplotypes were phased for 13 out of the 28 families and shared a conserved region of ∼3.6 Mb. Based on the mutation and recombination events observed in the microsatellite haplotypes and assuming a generation time of 25 years, the age estimate for the MSH2 mutation was 273 ± 64 years. The geographic origins of these families were mostly from the Northern region of Portugal. Concluding, these results suggest that the MSH2 c.2152C>T alteration is a founder mutation in Portugal with a relatively recent origin. Furthermore, its high proportion indicates that screening for this mutation as a first step, together with the previously reported Portuguese founder mutations, may be cost‐effective in genetic testing of Lynch syndrome suspects of Portuguese ancestry.